Are we addressing the knowledge translation needs of community-based organisations? A mixed-methods study. (1st July 2019) - Tobah, Selma; Kothari, Anita; Britten, Nicole; LeMoine, Karen
Abstract : In 2013, a knowledge translation (KT) strategy, PeelThinkShare, was created to strengthen evidence-based decision making among select community-based organisations (CBOs) located in the Regional Municipality of Peel in Ottawa, Canada. This article reports on the extent of PeelThinkShare's success, and those elements requiring further improvement. Using a mixed-methods design, including surveys and focus groups, the KT strategy was found to support the planning and practice of evidence-based services, and supported the evaluation of participating organisations' own services. The CBOs appreciated PeelThinkShare and expressed an interest in additional support to further their skills in implementing research evidence at a more detailed level. Repositories and one-stop evidence services need to be supplemented with skill-building forums to enhance CBOs' ability to use evidence. This study also confirmed the demand for informal, social learning-based opportunities such as networking. Further research is needed in the specific area of KT for CBOs.